Social status, gender, classroom climate and bullying among adolescents pupils - Cerezo, Fuensanta; Ato, Manuel (Anales de Psicología / Annals of Psychology, 2010)
This ex post facto study examines how the structure of the social relations (in sociometric and affective terms) and the social-affective class-room characteristics environment are related to bullying in 421 adoles-cents, aged 14 to 17, from 17 group classes of Spanish Secondary school (241 males and 180 females). Level of incidence (17.6%) was similar for bullies and victims. There were important differences by gender: three in four bullies and more than a half of the victims are boys. Multilevel analy-ses confirmed that all the classes displayed very similar characteristics of bullying behaviour. Findings indicated that those who are involved in bully/victim problems were usually males of lower social status, with a classroom climate perception more negative than neutral or not involved pupils, and, especially victim pupils showed serious difficulties in relation-ships. It was also found that girls are better adapted and more involved in the social climate of the classroom than boys. All that results suggest that social aspects contribute to maintain bullying among peers, and it may be a clue to explain why levels of bullying do not decrease and why the inci-dence is higher among boys than among girls.